Unveiling Sodium Diffusion Kinetics and Locking Mechanisms for High‐Performance CZTSSe Photovoltaics - Shuyu Li; Chaoran Li; Chu Liu; Jiachen Wu; Letu Siqin; Yuan Li; Guonan Cui; Yanchun Yang; Ruijian Liu; Hongmei Luan; Chengjun Zhu (Advanced Science)
Abstract This work unveils a diffusion‐kinetic modulation strategy that fundamentally redefines sodium management in kesterite photovoltaics, enabling spatially controlled Na sequestration within Cu2ZnSn(S,Se)4 (CZTSSe) absorber layers through a thermally engineered “Na‐locking” mechanism. By establishing critical correlations between post‐processing thermal protocols and alkali metal migration dynamics, how synchronized extension of sintering duration and rapid cooling termination creates a non‐equilibrium state that traps Na at strategic interfacial positions is demonstrated. This approach leverages Na's dual functionality as a crystallization promoter and defect passivator, driving concurrent improvements in crystallographic coherence and electronic uniformity. The optimized absorber architecture features laterally expanded grains with reduced boundary density and homogenized interfacial charge transport pathways, yielding the highest reported efficiency of 13.22% for Na‐doped CZTSSe solar cells to date, marked by synergistic enhancements in both VOC and FF. Crucially, this substrate‐derived Na regulation paradigm outperforms conventional extrinsic doping methods through its self‐limiting diffusion characteristics, ensuring compositional stability while eliminating secondary phase risks. The methodology establishes a universal framework for defect engineering in chalcogenide photovoltaics, bridging fundamental insights into alkali metal diffusion thermodynamics with scalable manufacturing solutions. These findings advance kesterite solar cell technology and offer a blueprint for optimizing thin‐film devices, improving process tolerance and material sustainability.